Modified chopped basalt fiber and preparation method thereof
By depositing calcium carbonate crystals on the surface of basalt fibers by Basilica Baspruri, the complexity and contamination of existing modification methods are solved, the tensile and compressive strength of cement-based materials is significantly improved, and a green and efficient process is achieved.
Patent Information
- Application Number
- CN202510324358.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-06-13
AI Technical Summary
The existing modification methods have problems such as complex process and environmental pollution in the surface treatment of basalt fibers, and the microbial calcium carbonate deposition technology used in basalt fibers has not been reported.
Basil Pasteurium metabolizes urea to generate carbonate ions, reacts with calcium salt to deposit calcium carbonate crystals on the fiber surface, forming a rough coating to improve the interface compatibility of the fiber surface.
Through the modified fibers, the 28d flexural strength of the cement-based material is increased by 27%, and the compressive strength is increased by 11%. The process is free of chemical pollution, simple operation, and low cost.
Smart Images

Figure CN120136471A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fiber - reinforced composite materials, and particularly relates to a modified chopped basalt fiber and a preparation method thereof. Background Art
[0002] In recent years, fiber - reinforced cement - based composites have been widely used in the field of construction engineering. The incorporation of fibers can effectively prevent the further expansion of micro - cracks in cement - based materials during the hardening process, and also play a role in bearing tensile stress in the materials, resulting in a significant increase in the overall tensile strength and flexural strength of the composites. Basalt fiber has the advantages of high tensile strength, high temperature resistance, corrosion resistance, and less pollution in the production process. Moreover, its composition is similar to that of cement - based materials, which can improve the mechanical properties of its composites.
[0003] At the same time, the workability of basalt fiber cement - based materials is better than that of composites with other fibers. The surface of basalt fiber is relatively smooth, resulting in poor interfacial compatibility with cement - based materials. When the cement - based material fractures or fails, the chopped basalt fiber is easily pulled out from the cement - based material. Different modification methods can be used to perform certain surface treatments on basalt fiber to improve the bonding ability between the fiber and the cement - based material. Existing modification methods (such as chemical etching and coupling agent treatment) have problems such as complex processes and environmental pollution. The microbial - induced calcium carbonate precipitation (MICP) technology has been used for material surface modification in recent years, but its application in basalt fiber has not been reported. Based on this, the present invention proposes a green and efficient biological modification method. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a preparation method for surface modification of basalt fiber in view of the deficiencies of the prior art. By using Sporosarcina pasteurii to metabolize urea to generate carbonate ions, which react with calcium salts to deposit calcium carbonate crystals on the fiber surface, a rough coating is formed on the surface of the chopped basalt fiber to improve the interfacial compatibility of the fiber surface. After being incorporated into the cement - based material, the strength of the cement - based material can be improved.
[0005] To solve the above - mentioned technical problems, the present invention discloses a preparation method for modified chopped basalt fiber, and the specific steps are as follows:
[0006] S1. Bacterial liquid preparation: Inoculate Sporosarcina pasteurii into a weakly alkaline culture medium and shake - culture to obtain a bacterial liquid;
[0007] S2. Mixture preparation: Mix the bacterial liquid and the nutrient solution and let it stand to obtain a mixture;
[0008] S3. Preparation of modified chopped basalt fiber: Immerse the chopped basalt fiber in the mixture, take it out and dry it to obtain the modified chopped basalt fiber.
[0009] Among them, in S1, the pH of the weakly alkaline culture medium is 8.0 - 10.0, and the specific formula of the weakly alkaline culture medium is: 20 g / L yeast powder, 10 g / L ammonium sulfate, 1.3 mg / L nickel chloride, and 1 L Tris buffer;
[0010] Preferably, in S1, the pH of the weakly alkaline culture medium is adjusted to 8.0 - 10.0 with sodium hydroxide solution, and after adjustment, it is sterilized at 120 °C for 20 min using an autoclave, and then Sporosarcina pasteurii is inoculated.
[0011] Among them, in S1, for the shaking culture, the specific conditions are: the temperature is controlled at 30 - 40 °C, the rotation speed is controlled at 150 - 200 r / min, and the culture duration is 24 h;
[0012] Preferably, in S1, for the shaking culture, the specific conditions are: the temperature is controlled at 40 °C, the rotation speed is controlled at 180 r / min, and the culture duration is 24 h.
[0013] Among them, in S1, the concentration of the bacterial liquid is 10 6 -10 7 cells / mL; preferably, in S1, the concentration of the bacterial liquid is 10 7 cells / mL.
[0014] Among them, in S2, the volume ratio of the bacterial liquid to the nutrient solution is 1:15.
[0015] Among them, the nutrient solution is a mixture of a calcium salt solution and a urea solution, and the volume ratio of the calcium salt solution to the urea solution is 1:1; the concentration of the calcium salt solution is 0.05 - 0.3 mol / L, and the concentration of the urea solution is 0.5 - 1.0 mol / L;
[0016] Preferably, the concentration of the calcium salt solution is 0.3 mol / L;
[0017] Preferably, the concentration of the urea solution is 0.5 mol / L.
[0018] Among them, the calcium salt includes CaCl 2 , Ca(NO 3 ) 2 ·4(H 2 O) and Ca(CH 3 COO) 2 ·H 2 O, or one or more of them;
[0019] Preferably, the calcium salt is CaCl 2 .
[0020] Among them, in S3, the chopped basalt fiber is obtained by high-speed drawing through a platinum-rhodium alloy wire-drawing bushing after the basalt material is melted at 145 - 1500 °C.
[0021] Among them, in S3, for the immersion, the specific conditions are: the immersion time is controlled within 24h - 48h.
[0022] Among them, in S3, for the drying, the specific conditions are: the drying temperature is controlled at 50 - 60 °C.
[0023] Furthermore, the modified chopped basalt fiber prepared by the above preparation method is also within the protection scope of the present invention; specifically, during the growth and reproduction of Sporosarcina pasteurii, urease is produced to rapidly hydrolyze urea to generate carbonate and ammonium ions, which combine with calcium ions to form a calcium carbonate crystal layer, and it is coated on the surface of the basalt fiber.
[0024] Furthermore, the application of the modified chopped basalt fiber prepared by the above preparation method in improving the tensile strength and flexural strength of cement-based materials is also within the protection scope of the present invention;
[0025] Specifically, in some embodiments of the present invention, the modified chopped basalt fiber was successfully prepared by the above preparation method, and the modified chopped basalt fiber, reference cement, and standard sand were used to prepare test mortar. After molding, the 28-day flexural strength and compressive strength were tested. Experiments showed that the 28-day flexural strength of the fiber-reinforced cement-based material after modification could be increased to a maximum of 9.8 MPa, and the compressive strength was increased to 53.8 MPa, which were 27% and 11% higher than those of the unmodified fiber respectively, and had a greater effect on improving the performance of the cement-based material, demonstrating the application prospect of the above modified chopped basalt in improving the tensile strength and flexural strength of cement-based materials.
[0026] Beneficial effects:
[0027] 1. Basalt fiber is a continuous fiber drawn from natural basalt and is an inorganic material. The calcite and vaterite crystals mineralized and deposited on the surface of the chopped basalt fiber by microorganisms are also inorganic materials. The compatibility and binding ability between the two are better, which is beneficial to improving the interfacial compatibility of cement-based composites;
[0028] 2. The surface roughness of the modified fiber is significantly improved, and the binding force with the cement-based material is enhanced;
[0029] 3. The 28-day flexural strength of the cement mortar using the modified fiber is increased by up to 27% at most, and the compressive strength is increased by up to 11% at most;
[0030] 4. The process has no chemical pollution, is simple to operate, and has low cost. Description of the Drawings
[0031] The following further specific description of the present invention will be made in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become clearer.
[0032] Figure 1 This is a 1000-fold electron microscope image of the surface of the modified chopped basalt fiber in Example 1 of the present invention.
[0033] Figure 2 This is a 5000-fold electron microscope image of the surface of the modified chopped basalt fiber in Example 1 of the present invention.
[0034] Figure 3 This is a 1000-fold electron microscope image of the surface of the unmodified chopped basalt fiber in Comparative Example 1 of the present invention.
[0035] Figure 4 This is a 10000-fold electron microscope image of the surface of the unmodified chopped basalt fiber in Comparative Example 1 of the present invention. Specific Embodiments
[0036] In the following examples, the experimental methods are all conventional methods unless otherwise specified; the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0037] The strain used in the following examples is Sporosarcina pasteurii, purchased from the American Type Culture Collection (ATCC), with the number ATCC 11859.
[0038] Example 1:
[0039] Prepare the culture medium required for microorganisms, and culture it using a chloride-based medium and the No. 1376 medium recommended by ATCC. Its main components are 20 g / L yeast powder, 10 g / L ammonium sulfate, 1 L Tris buffer, and 1.3 mg / L nickel chloride; adjust the pH value of the culture medium to 9.0 with sodium hydroxide solution; after sterilizing at 120 °C for 20 min using an autoclave, inoculate Sporosarcina pasteurii into the culture medium, and the concentration of the bacterial solution is 10 7 cells / mL, place it in a constant temperature shaker, control the temperature at 40 °C, the rotation speed is 180 r / min, and shake and culture for 24 h to obtain the cultured bacterial solution. Keep the whole culture process aseptic;
[0040] Mix the calcium salt solution and the urea solution in a volume ratio of 1:1 to obtain a nutrient solution. Among them, the calcium salt is CaCl 2, with a concentration of 0.3 mol / L and the solvent being distilled water or deionized water; the concentration of urea is 0.5 mol / L and the solvent is distilled water or deionized water. The cultured bacterial liquid and the nutrient solution are mixed at a volume ratio of 1:15 to obtain a mixed solution. After standing for 2 h, the short-cut basalt fibers are evenly immersed in the mixed solution, and the infiltration time is controlled within 24 h to 48 h; after taking out the short-cut basalt fibers from the mixed solution, the drying temperature is controlled at 50 - 60 °C to obtain modified short-cut basalt fibers.
[0041] Mix 450 g of reference cement and 1350 g of standard sand for 30 s, then add 2.63 g of modified short-cut basalt fibers and mix for 30 s, add 225 g of water and mix. After molding, test the 28-day flexural strength and compressive strength of the mortar.
[0042] Example 2:
[0043] Adjust the concentration of the bacterial liquid of Sarcina pasteurii inoculated into the culture medium in Example 1 to 10 6 cells / mL, with other steps unchanged, prepare the corresponding mortar, and test the 28-day flexural strength and compressive strength of the mortar after molding.
[0044] Example 3:
[0045] Adjust the pH value of the culture medium to 8.0 with sodium hydroxide solution in Example 1, with other steps unchanged, prepare the corresponding mortar, and test the 28-day flexural strength and compressive strength of the mortar after molding.
[0046] Example 4:
[0047] Adjust the calcium salt concentration in the nutrient solution to 0.05 mol / L in Example 1, with other steps unchanged, prepare the corresponding mortar, and test the 28-day flexural strength and compressive strength of the mortar after molding.
[0048] Comparative Example 1:
[0049] Mix 450 g of reference cement and 1350 g of standard sand for 30 s, then add 2.63 g of unmodified short-cut basalt fibers and mix for 30 s, add 225 g of water and mix. After molding, test the 28-day flexural strength and compressive strength of the mortar.
[0050] Performance Characterization:
[0051] Use a scanning electron microscope to respectively characterize the microscopic morphology of the modified short-cut basalt fibers in Example 1 and the unmodified short-cut basalt fibers in Comparative Example 1. Figure 1 is the 1000-fold electron microscope image of the surface of the modified short-cut basalt fibers in Example 1. Figure 2 is the 5000-fold electron microscope image of the surface of the modified short-cut basalt fibers in Example 1. Figure 3It is the SEM image with 1000 times magnification of the surface of the unmodified chopped basalt fibers in Comparative Example 1. Figure 4 It is the SEM image with 10000 times magnification of the surface of the unmodified chopped basalt fibers in Comparative Example 1, Figures 1 to 4 It can be seen that uniform calcium carbonate crystals are visible on the surface of the chopped basalt fibers after microbial modification, and the crystal morphology is clear. There is no crystal coverage on the surface of the unmodified chopped basalt fibers. After magnification, it can be seen that the surface of a single fiber is relatively smooth, and the bonding with the matrix in the mortar is weak, unable to form a synergistic effect, resulting in an insignificant fiber reinforcement and toughening effect.
[0052] The results of the flexural strength and compressive strength of the mortars in Examples 1 to 4 and Comparative Example 1 after 28 days of molding are shown in Table 1 below:
[0053] Table 1 Flexural strength and compressive strength of the mortars in Examples 1 to 4 and Comparative Example 1 after 28 days of molding
[0054] Item Flexural strength at 28d (MPa) Compressive strength at 28d (MPa) Example 1 9.8 53.8 Example 2 8.9 47.1 Example 3 9.2 50.4 Example 4 8.6 49.9 Comparative Example 1 7.7 48.6
[0055] It can be seen from the data in Table 1 that the mortars in Examples 1 to 4 have better mechanical properties compared to the mortar in Comparative Example 1. Among them, the optimal solution can increase the 28-day flexural strength of the cement mortar by 27% and the compressive strength by 11%. The strength of the mortar in Example 2 is significantly lower than that in Example 1, indicating that a high bacterial solution concentration is crucial for the mineralization efficiency. Compared with the mortar in Example 1, the compressive strength and flexural strength of the mortar in Example 3 both decrease. The main difference is that the pH value in Example 3 is lower than that in Example 1. Under certain alkaline conditions, the growth activity of the medium is stronger, and it can adhere to the fiber surface more actively, forming more calcium carbonate deposits. Therefore, due to the decrease in pH value in Example 3, the amount of calcium carbonate deposition is insufficient, and the interface improvement effect is limited. Compared with the mortar in Example 1, the compressive strength and flexural strength of the mortar in Example 4 both decrease. The main difference is that the calcium salt concentration in the nutrient solution in Example 4 is lower than that in Example 1, and the corresponding calcium source cannot provide sufficient raw materials for calcium carbonate deposition, resulting in the crystal coverage rate on the fiber surface in Example 4 being lower than that in Example 1, and the improvement of mechanical properties being limited.
[0056] The present invention provides a modified chopped basalt fiber and its preparation method. There are many methods and ways to specifically implement this technical solution. The above is only the preferred implementation manner of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention. Each component not clearly defined in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing modified chopped basalt fiber, characterized in that: The specific steps are: S1. Preparation of bacterial solution: inoculate Bacillus pasteurianus into a weakly alkaline culture medium and culture under shaking to obtain a bacterial solution; S2. Preparation of mixed solution: Mix the bacterial solution and the nutrient solution and let stand to obtain a mixed solution; S3. Preparation of modified chopped basalt fibers: immersing the chopped basalt fibers in the mixed solution, taking them out and drying them to obtain the modified chopped basalt fibers.
2. The preparation method according to claim 1, characterized in that: In S1, the pH of the weak alkaline culture medium is 8.0-10.0, and the specific formula of the weak alkaline culture medium is: 20 g / L yeast powder, 10 g / L ammonium sulfate, 1.3 mg / L nickel chloride and 1 L Tris buffer.
3. The preparation method according to claim 1, characterized in that: In S1, the shaking culture has the following specific conditions: the temperature is controlled at 30-40°C, the rotation speed is controlled at 150-200 r / min, and the culture time is 24 h.
4. The preparation method according to claim 1, characterized in that: In S1, the concentration of the bacterial solution is 10 6 ~10 7 Pieces / mL.
5. The preparation method according to claim 1, characterized in that: In S2, the volume ratio of the bacterial liquid to the nutrient solution is 1:
15.
6. The preparation method according to claim 5, characterized in that: The nutrient solution is a mixture of a calcium salt solution and a urea solution, wherein the volume ratio of the calcium salt solution to the urea solution is 1:1; the concentration of the calcium salt solution is 0.05-0.3 mol / L, and the concentration of the urea solution is 0.5-1.0 mol / L.
7. The preparation method according to claim 6, characterized in that: The calcium salt includes one or more of CaCl2, Ca(NO3)2·4(H2O) and Ca(CH3COO)2·H2O.
8. The preparation method according to claim 1, characterized in that: In S3, the immersion has the following specific conditions: the immersion time is controlled within 24h to 48h.
9. The modified chopped basalt fiber prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the modified chopped basalt fiber according to claim 9 in improving the tensile strength and flexural strength of cement-based materials.
Citation Information
Cited By
All-solid waste lightweight aggregate grouting material as well as preparation method and application thereof
CN122145123A